Genome-wide analysis and identification of the TBL gene family in Eucalyptus grandis - Tang, Jiye; Ling, Tenghong; Li, Huiling; Fan, Chunjie (Frontiers in Plant Science, 2024)
The TRICHOME BIREFRINGENCE-LIKE (TBL) gene encodes a class of proteins related to xylan acetylation, which has been shown to play an important role in plant response to environmental stresses. This gene family has been meticulously investigated in Arabidopsis thaliana, whereas there have been no related reports in Eucalyptus grandis. In this study, we identified 49 TBL genes in E. grandis. A conserved amino acid motif was identified, which plays an important role in the execution of the function of TBL gene family member. The expression of TBL genes was generally up-regulated in jasmonic acid-treated experiments, whereas it has been found that jasmonic acid activates the expression of genes involved in the defense functions of the plant body, suggesting that TBL genes play an important function in the response of the plant to stress. The principle of the action of TBL genes is supported by the finding that the xylan acetylation process increases the rigidity of the cell wall of the plant body and thus improves the plant's resistance to stress. The results of this study provide new information about the TBL gene family in E. grandis and will help in the study of the evolution, inheritance and function of TBL genes in E. grandis, while confirming their functions.